2018
DOI: 10.3892/mmr.2018.8999
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields inhibit osteoclast differentiation in RAW264.7 macrophages via suppression of the protein kinase B/mammalian target of rapamycin signaling pathway

Abstract: When bone resorption, aided by the activity of osteoclasts, exceeds bone formation induced by osteoblasts, bone metabolism loses equilibration, which results in the development of bone diseases, including osteoporosis. Pulsed electromagnetic fields (PEMFs) are known to be involved in various biological processes, including cell proliferation, differentiation and apoptosis. However, the exact mechanism of action of osteoclasts remains poorly understood. In the present study, the effects of PEMFs on osteoclast d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…By inducing ROS, ELF-PEMF thus may favor osteoclastogenesis, an assumption supported by the studies of Pi and Zhang [64,65]. However, there are also several other reports showing ELF-PEMF inhibitory effects on osteoclastogenesis [66][67][68]. He et al suggest that ELF-PEMF suppressive effects are mediated by endocrine effects of osteoblasts [67], a hypothesis supported by several other studies [61,[69][70][71][72].…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 83%
“…By inducing ROS, ELF-PEMF thus may favor osteoclastogenesis, an assumption supported by the studies of Pi and Zhang [64,65]. However, there are also several other reports showing ELF-PEMF inhibitory effects on osteoclastogenesis [66][67][68]. He et al suggest that ELF-PEMF suppressive effects are mediated by endocrine effects of osteoblasts [67], a hypothesis supported by several other studies [61,[69][70][71][72].…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 83%
“…Normally, dentine or bone slices are used to evaluate osteoclast differentiation and function (20,43), however, they are difficult to handle and easily damaged. The Corning Osteo Assay Surface represents a convenient and reproducible substitute for slices (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Ying Pi et al found that a low-frequency PEMF inhibits osteoclast differentiation by scavenging reactive oxygen species, and it is a potential treatment for osteoporosis [ 60 ]. Yutian Lei et al found that PEMFs inhibit osteoclast differentiation and inhibit the progression of osteoporosis by regulating the Akt/mTOR signaling pathway [ 61 ]. Moreover, many other researchers have found that PEMFs inhibit the progression of osteoporosis by inhibiting osteoclast formation and differentiation [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Pemfs For Osteoporosismentioning
confidence: 99%